2021
DOI: 10.1128/mcb.00449-20
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring of Lactate–Interleukin-1β Autoregulatory Loop with Clock-Bmal1: a Feed-Forward Circuit in Glioma

Abstract: De-synchronized circadian rhythm in tumors is coincident with aberrant inflammation and dysregulated metabolism. As their inter-relationship in cancer etiology is largely unknown, we investigated the link between the three in glioma. Tumor metabolite lactate- mediated increase in pro-inflammatory cytokine IL-1β was concomitant with elevated levels of core circadian regulators Clock and Bmal1. siRNA mediated knockdown of Bmal1 and Clock decreased (i) LDHA and IL-1β levels and (ii) release of lactate and pro-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…While ICuRuS can determine H3K4me3/H3K27me3 coenrichment at specific loci, it cannot determine if these marks occur on the same histone or nucleosome. An alternative approach to study H3K4me3/H3K27me3 bivalency is sequential ChIP, which determines hPTM localization on the same nucleosome 45 . Overall, ICuRuS provides technological advances to understand epigenetic regulation in other neural disorders, brain regions, and cell-types A2a and D1 MSNs make up ~95% of the neuronal population in the striatum 46 .…”
Section: Discussionmentioning
confidence: 99%
“…While ICuRuS can determine H3K4me3/H3K27me3 coenrichment at specific loci, it cannot determine if these marks occur on the same histone or nucleosome. An alternative approach to study H3K4me3/H3K27me3 bivalency is sequential ChIP, which determines hPTM localization on the same nucleosome 45 . Overall, ICuRuS provides technological advances to understand epigenetic regulation in other neural disorders, brain regions, and cell-types A2a and D1 MSNs make up ~95% of the neuronal population in the striatum 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In more detail, CLOCK increased the expression of cyclins A, B1 , and D1 due to its histone transferase activity and activated the NF-κB (Nuclear Factor kappa B) pathway. Its expression was de-repressed in GBM by downregulation of miR-124 (microRNA-124) 17 , 19 . Notably, a study performed by Dong et al found that downregulation of CLOCK/BMAL1 negatively affected proliferation and cell cycle progression in Glioblastoma Stem Cells (GSCs) but not in Neural Stem Cells (NSCs) 16 .…”
Section: Impact Of the Circadian Clock On Gbm Cell Proliferation And ...mentioning
confidence: 99%
“…3b ). The function of CLOCK/BMAL1 in oxidative stress regulation and DNA damage repair under normal conditions i.e., without external stress induction is controversial in experimental studies 17 , 19 21 . In a computational study using TCGA (The Cancer Genome Atlas) glioma data, CRY1 , BMAL1 , and RORγ were associated with a higher mutation rate and mutation hotspots in EGFR , TTN (Titin) , and PTEN (Phosphatase and Tensin Homologue) genes.…”
Section: Impact Of the Clock On Stress Response Dna Damage Control An...mentioning
confidence: 99%
“…A desynchronized circadian rhythm in tumors is coincident with aberrant inflammation and dysregulated metabolism 105 . The increase in tumor metabolite lactate results in the cytokine interleukin‐1β (IL‐1β) upregulation leading to inflammatory 106 . IL‐1β was correlated with elevated levels of the core circadian regulators Clock and Bmal1 106 .…”
Section: The Molecular Pathways Involved In Glioma Circadian Clockmentioning
confidence: 99%
“…The increase in tumor metabolite lactate results in the cytokine interleukin‐1β (IL‐1β) upregulation leading to inflammatory 106 . IL‐1β was correlated with elevated levels of the core circadian regulators Clock and Bmal1 106 . Lactate‐IL‐1β interaction positively affects the recruitment of CLOCK: BMAL1 to these E‐box sites in the nucleus 107 .…”
Section: The Molecular Pathways Involved In Glioma Circadian Clockmentioning
confidence: 99%